Effect of Cd(II) on Different Bacterial Species Present in a Single Sludge Activated Sludge Process for Carbon and Nutrient Removal - Tsai, Yung-Pin; You, Sheng-Jie; Pai, Tzu-Yi; Chen, Ko-Wei (Journal of environmental engineering (New York, N.Y.), 2006)
Heavy metal cadmium(II) was added stepwise into an A2 O pilot plant to investigate the toxic effects of Cd(II) on the removal efficiencies, kinetic parameters (yield coefficients and maximum specific growth rates) and reaction rates of carbon, nitrogen and phosphate for the acclimatized heterotrophic and autotrophic bacteria. Results showed that 2 mg∕L Cd(II) initially affected the biological reaction of phosphate removal. At Cd(II) 5 mg∕L , the efficiencies of total nitrogen removal and nitrification were substantially dropped. At the same time, the yield coefficient and maximum specific growth rate of heterotrophs were significantly decreased from 0.8 g COD∕g COD and 6.44 day−1 to 0.54 g COD∕g COD and 4.67 day−1 , respectively. And, the denitrification rate was inhibited by about 61%. The inhibition percentages of anaerobic release, anoxic and aerobic uptake rates of phosphate were about 76, 64, and 90%, respectively. When Cd(II) concentration was continually increased up to 35 mg∕L , removal efficiency of chemical oxygen demand (COD) was significantly dropped. However, there was no obvious inhibition on the biological reactions of anaerobic ammonification.